ALIENATION’S COMPLEX OF RELATIONS: GENESIS AND TRANSFORMATIONS - Shedyakov, Vladimir (Collection of scientific papers «ΛΌГOΣ», 2023)
Alienation as a complex of relations has material (primarily political-economic and technical-technological), sociocultural and moral-spiritual prerequisites, and each component’s role is variable [1-5]. The complex of relations of alienation is formed on the material-object, social-material and social-ideal levels, fixing the quality of mutual representation of objective and subjective phenomena. When living activity is additional to the past, real and future work of other members of society and its meaning is determined by collective work, then a person relates to the world of visibility first through collective and only then – through his living work. Pre-reflective consciousness replaces the truth of essential being with the plausibility of the world of illusions, that second reality, "own world", which is generated by the fetishism of being itself. The complex of alienation’ relations connect a position that is neutral to people’s assessment, characterized natural process of increasing individual’s isolation, with a negatively assessed destruction of personality. The first aspect (the so-called "positive alienation", "indifferent alienation", "objectification") is a necessary moment for the deployment of essential forces, their self-determination as a source of additional social strength, the content of universal wealth and the prerequisites for social labour, the basis for the transition from activities of adaptation and appropriation of the surrounding world to production labour. The second aspect (alienation in the narrow sense of the word) is the assimilation by society of only a small part of human potential, which is selected randomly, spontaneously.